BUILDING LEARNING COMMUNICATION STRATEGIES IN THE COVID-19 PANDEMIC ERA - Puspa Dewi; Basuki Basuki (Jurnal Bahtera: Jurnal Pendidikan, Bahasa, Sastra, dan Budaya, 2022)
Given the significance of communication's role and function, namely as a bridge/message between the communicator (message sender) and the communicant (message recipient), an effective communication strategy is required so that communication can run meaningfully. Regarding the role and function of communication in the learning process, this is a note for teachers that should be considered. This research aims to provide benefits, particularly for teachers, so that they can implement effective communication strategies during the learning process in the pandemic era. This study employs qualitative research methods. This study employs a qualitative approach based on the literature review methodology. Several components must be considered when  implementing effective communication strategies in the learning process, including: 1) Systematic communication, 2) Communication methods for learning: how to organize messages so that the learning process works effectively and efficiently, and communication methods for learning: how to organize messages so that the learning process works effectively and efficiently. 3) Communication channels 4). Time management. In short, communication is effective when the sender's message conveys the same meaning as the message received and understood by the recipient. Similarly, communication with students, as a facilitator or imparter of knowledge, must be established so that the message conveyed can be well received by students, utilizing a variety of skills and efforts.